Micro-Finance, Women's Empowerment and Fertility Decline in Bangladesh: How Important Was Women's Agency?. Issue 5 (4th May 2017) - Duvendack, Maren; Palmer-Jones, Richard
Abstract: As Nobel Prize winner Amartya Sen has argued "[Bangladesh's development achievements have] important lessons for other countries across the globe, [in particular a focus on] reducing gender inequality". A major avenue through which this emphasis has been manifest lies, according to this narrative, in enhancements to women's agency for instrumental and intrinsic reasons particularly through innovations in family planning and microfinance. The "Bangladesh paradox" of improved wellbeing despite low economic growth over the last four decades is claimed as a paradigmatic case of the spread of both modern family planning programmes and microfinance leading to women's empowerment and fertility reduction. In this paper we show that the links between microfinance, empowerment and fertility reduction, are fraught with problems, and far from robust; hence the claimed causal links between microfinance and family planning via women's empowerment needs to be further reconsidered.